2020
DOI: 10.2169/internalmedicine.4701-20
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren's Syndrome as an Immune-related Adverse Event of Nivolumab Treatment for Gastric Cancer

Abstract: Immune checkpoint inhibitors can affect any organ, including the salivary glands. A case of Sjögren's syndrome (SjS) induced by nivolumab for the treatment of gastric cancer is herein presented. Nivolumab treatment caused marked tumor shrinkage, but xerostomia developed after two cycles. It took 3 months after symptom onset to confirm the diagnosis of SjS. Prednisolone and pilocarpine hydrochloride did not relieve the symptoms. SjS is a relatively rare immune-related adverse event that might sometimes be overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In a study on ICI-induced Sicca syndrome, most infiltrating cells were T cells, with more CD4 + T cells than CD8 + T cells and only a few CD20 + B cells [98]. A histological study of the lower lip mucosa revealed that although aggregated CD20 + B cells and CD3 + T cells were observed, T cells were predominant and the CD8 + T cell was more frequent than the CD4 + T cell [100]. This indicates that much lower levels of B cells infiltrate the salivary gland in ICI-induced Sicca syndrome compared with pSS.…”
Section: Induction Of Sicca Syndrome By Icismentioning
confidence: 99%
“…In a study on ICI-induced Sicca syndrome, most infiltrating cells were T cells, with more CD4 + T cells than CD8 + T cells and only a few CD20 + B cells [98]. A histological study of the lower lip mucosa revealed that although aggregated CD20 + B cells and CD3 + T cells were observed, T cells were predominant and the CD8 + T cell was more frequent than the CD4 + T cell [100]. This indicates that much lower levels of B cells infiltrate the salivary gland in ICI-induced Sicca syndrome compared with pSS.…”
Section: Induction Of Sicca Syndrome By Icismentioning
confidence: 99%
“…The mechanism of ICI-induced xerostomia is considered as an impairment of the PD-1/PD-L1 pathway caused by ICIs that trigger the activation of T-lymphocytes, leading to infiltration of the salivary gland epithelium [ 8 , 9 ]. As a result, it is suggested that there is a lack of the salivary acinar cells and salivary dysfunction is caused [ 10 ].…”
Section: Introductionmentioning
confidence: 99%